Study in Surat (Q) (Journal of the College of Basic Education, 2023)
The research, tagged with (a study in Surat Q), consists of four topics, which are as follows:The first: the phonetic study - in which the sonic phenomena are manifested, such as: vocal harmony; and homogeneityPhonetics, metaphors, diphthongs, stress and syllables, and verse breaks that come to leadA vocal and spiritual purpose at the same time.The second: the morphological topic - and it contains the doors of the abstract triple verb; And what was said in some morphological issues;And then the crowds of all kinds, as well as a lot of anecdotes.The third: the linguistic and grammatical topic - it includes several linguistic and grammatical issues, including: saying in (Q)And the reference, and the addition of the thing to itself, and the reminder and the feminization and the saying in the address T; and deleteeffect.The fourth: the rhetorical topic - it includes creative improvements and forms of eloquence. It is the benefactorsAl-Badi'iyah: Anaphora, counterpoint, assonance, plural, division, and attention. Among the types of statement: metaphorMental metaphor, transmitted metaphor, analogy and metaphor of all kinds, such as declarative and mechanical metaphorand charade.